Analyzing The Impact of Contract Value, Project Duration, and Number of Floors on Human Resource Costs In The Agenci Dejenvolvementu Nacional Office Construction Project In Dili Using Multiple Regression - Raimundo, João; Witjaksana, Budi; Purnama, Jaka (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the influence of building construction project financing, which includes contract value, project duration, and number of floors, on human resource costs (Expert Costs, Skilled Labor Costs, and Worker/Mandor Costs) in building construction projects within the Dili City Government Office. The research focuses on 20 building projects in the Dili City Government Office environment. Using project report documents as data, the independent variables in this study are contract value, project duration, and the number of floors, while the dependent variables are the costs associated with experts, skilled labor, and workers/mandors/laden. The study employs multiple linear regression analysis to assess the relationship between these variables. The results show that the contract value has a significant partial effect on human resource costs, including expert costs, skilled labor costs, and worker/mandor costs. This indicates that a higher contract value influences the allocation of human resource costs in building construction projects. In conclusion, the study highlights the importance of managing contract value, project duration, and the number of floors to optimize human resource costs and ensure efficient project completion.